Inflammation–coagulation response and thrombotic effects induced by silica nanoparticles in zebrafish embryos - Duan, Junchao (Nanotoxicology, 2018)
Nowadays, nanotechnology environmental health and safety (nanoEHS) is gaining attention. We previously found that silica nanoparticles (SiNPs) could induce vascular endothelial damage. However, the subsequent toxicologic response to SiNPs-induced endothelial damage was still largely unknown. In this study, we explored the inflammation–coagulation response and thrombotic effects of SiNPs in endothelial cells and zebrafish embryos. For in vitro study, swollen mitochondria and autophagosome were observed in ultrastructural analysis. The cytoskeleton organization was disrupted by SiNPs in vascular endothelial cells. The release of proinflammatory and procoagulant cytokines including IL-6, IL-8, MCP-1, PECAM-1, TF and vWF, were markedly elevated in a dose-dependent manner. For in vivo study, based on the NOAEL for dosimetry selection, and using two transgenic zebrafish, Tg(mpo:GFP) and Tg(fli-1:EGFP), SiNPs-induced neutrophil-mediated inflammation and impaired vascular endothelial cells. With the dosage higher than NOAEL, SiNPs significantly decreased blood flow and velocity, exhibiting a blood hypercoagulable state in zebrafish embryos. The thrombotic effect was assessed by o-dianisidine staining, showed that an increasing of erythrocyte aggregation occurred in SiNPs-treated zebrafish. Microarray analysis was used to screen the possible genes for inflammation–coagulation response to SiNPs in zebrafish, and the JAK1/TF signaling pathway was further verified by qRT-PCR and Western blot assays. For in-deepth study, il6st was knocked down with specific morpholinos. The whole-mount in situ hybridization and qRT-PCR analysis showed that the expression jak1 and f3b were attenuated in il6st knockdown groups. In summary, our data demonstrated that SiNPs could induce inflammation–coagulation response and thrombotic effects via JAK1/TF signaling pathway.